Examiners' malpractice dispositions: paradigm of assessment quality (2011)
Quality of certificates awarded by any examining body is determined by the adequacy of its examination processes, which include: test development, examination conduct, marking exercise and score collation. Apart from score collation stage, external individuals are usuallybrought in, 'at other stages, and the disposition of such people can either make or mar the process: This study therefore investigated disposition of the examiners for both the West African Examinations Council (WAEC) and NationaI Examimition Council (NEeD) towards Examinationrnal practice. Efforts were also made to determine the factors that can influencesuch disposition significantly among examiners' and school variables. Cluster sampling technique was employed to Select seven hundred and sixty three examiners during WAEC and NECO marking Exercise from three Geo-Political Zones in Nigeria. A questionnaire Marking exercise (Cronbach Alpha Reliability Coefficient = 0.60) and Examiners Disposition to Malpractice (Cronbach Alpha Reliability Coefficient = 0.83). The result shows that, above 30 percent of the sampled examiners indicated 'poor incentive' and 'attitude of officials of the examining bodies' as the major reasons for not reporting cases of examination malpractice comprising two subscales, Attitude Towards (missing sentences) sampled examiners had poor disposition towards reporting malpractice cases. Among he ten examiners and Examiners' school variables regressed against examiners' disposition, they all had composite influence on Examiners' disposition (R=.269; Adjusted R2:.055; F(5.5I 7)=4·05;p<.05). It was however found that, only Examined;' attitude to marking (β=230; t=5.391; P<O.05)and Years of Marking with WAEC (β.l55; t=2.042;P<O.05)were significant factors that positively influenced examiners' disposition to reporting cases of examination malpractice. The findings have implication for examining bodies and all stakeholders in education business. Examining bodies should not rely only on coordination exercises as the only medium of contact with examiners, but organize workshops and seminars for examiners where issues that centre on examination malpractice and ill effect would be discussed.